Penerapan Model Problem Based Learning pada Pembelajaran Tematik untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Zahra, Nitya Az; Antosa, Zariul; Guslinda, Guslinda (ARZUSIN, 2023)
This research was motivated by the low thematic learning outcomes of students. This study aims to determine whether the application of the Problem Based Learning model can improve student learning outcomes in elementary schools. research is a qualitative and quantitative research conducted using Classroom Action Research (PTK) for 2 cycles. The research subjects were fifth grade students of SD Negeri 03 Pandam Gadang. This research was conducted in 4 stages, namely planning, implementation, observation and reflection. This research data collection technique consists of observation, tests and documentation of research instruments are observation, tests and non-tests. The results showed an increase seen from (1) Assessment of teacher activities in cycle I 82.14% good qualifications (B), cycle II to 92.85% very good qualifications (SB) because the implementation of learning carried out has fulfilled the steps of the Problem Based Learning model. (2) Assessment of student activities in cycle I average student score 65.73 with sufficient predicate (C), cycle II 80.83 with good predicate (B). (3) Assessment of student learning outcomes in cycle 1 average student score 65.73 with a predicate of sufficient (C), cycle II 80.83 with a predicate of good (B). It can be concluded that the application of the Problem Based Learning model can improve the learning outcomes of grade V students in elementary schools.